A note on imposing strong complementary in DEA - Vladimir Krivonozhko; Finn R. Førsund; Andrey V. Lychev (University of Oslo, Department of Economics, 2010)
A new DEA model has been introduced recently combining the primal and the dual models in order to impose strong complementary slackness conditions. It was claimed that a reference set that contains the maximum number of efficient units can then be determined. The model is very interesting as a theoretical idea. However, not only does the computational burden increase significantly, but it seems also that the basic matrices may be inherently ill-conditioned, leading to wrong results. Numerical experiments have been carried out on two real datasets of medium size with 163 and 920 units. These experiments show pervasive existence of ill-conditioned matrices leading to obviously wrong estimates of efficiency scores, and units declared as efficient reference units while actually being inefficient.
Keywords: C61; D20; 330; Data envelopment analysis; BCC model; DEA/SCSC model; strong complementary slackness conditions